2021
DOI: 10.1093/ajcn/nqab199
|View full text |Cite
|
Sign up to set email alerts
|

Plasma choline and betaine and risks of cardiovascular events and recurrent stroke after ischemic stroke

Abstract: Background Choline and betaine have been suggested to play a pivotal role in neurotransmitter synthesis, cell membrane integrity, and methyl-group metabolism, exerting neuroprotective effects in patients with various neurological disorders. However, population-based evidence on choline and betaine with subsequent cardiovascular events after stroke is rare. Objectives We aimed to prospectively investigate the relationships of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…However, result of a case–control study from Chinese patients indicated that plasma choline was inversely associated with recurrent stroke in the setting of ischemic stroke. 19 In the present study, we observed that elevated plasma levels of TMAO and choline were associated with an increased risk of recurrent stroke in the cohort of CNSR‐III, which is a nationwide prospective registry for patients presenting to hospitals with acute ischemic cerebrovascular events.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…However, result of a case–control study from Chinese patients indicated that plasma choline was inversely associated with recurrent stroke in the setting of ischemic stroke. 19 In the present study, we observed that elevated plasma levels of TMAO and choline were associated with an increased risk of recurrent stroke in the cohort of CNSR‐III, which is a nationwide prospective registry for patients presenting to hospitals with acute ischemic cerebrovascular events.…”
Section: Discussionmentioning
confidence: 49%
“…Although some studies have also investigated the association of TMAO and choline with stroke recurrence in the secondary prevention population of ischemic stroke, the results are not consistent. 5 , 18 , 19 Haghikia et al 5 demonstrated that patients with elevated TMAO levels, but not choline, were at higher risk of recurrent stroke over 1‐year follow‐up. However, result of a case–control study from Chinese patients indicated that plasma choline was inversely associated with recurrent stroke in the setting of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, choline deficiency increases the activity of acetylcholinesterase ( 21 ), and serum cholinesterase activities reflect the intensity of the neuroinflammatory response in patients with stroke ( 22 ). Moreover, choline and betaine are metabolites of the choline pathway associated with decreased cardiovascular risks and recurrent strokes ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Betaine is an oxidation product of choline, which is linked to folate and serves as a methyl donor in one-carbon metabolism ( 12 , 14 , 25 ). A low concentration of betaine is associated with a number of stroke risk factors, such as insulin resistance, diabetes mellitus, lipid metabolism, and atherogenic dyslipidemia ( 24 , 26 28 ). In the current study, we observed an inverse relationship between betaine and risk of MMD and its subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The sample preparation for measurements of plasma carnitine, choline, betaine, TML, TMAO, and cotinine (a biomarker of recent nicotine exposure) has been mentioned by a previous report [27]. These metabolites were measured by an ultrahigh performance liquid chromatography–tandem mass spectrometry platform [28].…”
Section: Methodsmentioning
confidence: 99%